Hubungan Pendidikan, Pengetahuan, Pendapatan Keluarga dan Pemanfaatan Fasilitas Kesehatan Terhadap Kejadian Stunting Pada Balita di Kabupaten Kapuas Tahun 2021 - Mayae Hugo; Kristie Hapsari (POLITEKNIK KESEHATAN KEMENKES PALANGKA RAYA, 2023)
Stunting is caused by lack of nutritional intake in a long time due to feeding that is not in accordance with the needs of micro nutrition. Stunting can occur starting the fetus is still in the womb and only appears when a child is two years old. Research Objectives To determine the relationship of education, knowledge about nutrition, family income and the use of facilities with the occurrence of stunting in toddlers in Kapuas Regency. Types of correlation research with cross-sectional design. The population is all mothers who have stunting toddlers in the Kapuas Regency EPPGBM application, which is 2,480 children. The number of samples 344, using the Slovin Data formula was analyzed by the Chi-Square test, with a significant level of P> 0.05 (95%confidence level). The results of bivariate analysis show that there is no relationship between education and stunting (p = 0.613) and there is a relationship between knowledge (p = 0.022), family income (p = 0.036) and utilizing health facilities (p = 0.002) with stunting. To overcome the problem of stunting, the role of BBKBN of Central Kalimantan Province through PKB/PLKB personnel to provide support and assistance and non -formal learning to families, adolescents, prospective fertile age pairs or community groups in an effort to increase knowledge and changes in behavior related to childcare, and help provide Motivation to families and promotions about the importance of utilizing health facilities, especially to prevent stunting by monitoring the growth and development of toddlers regularly.